SOSIALISASI KEHIDUPAN KAMPUS BAGI MAHASISWA BARU FISIP UNIVERSITAS MULAWARMAN - Bharata, Wira; Rahmawati, Alia; Rahayu, Diah; Juwita, Rina; Daryono, Daryono (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The transition from adolescence to adulthood often poses significant challenges for new students, especially during the transition from high school to college. This community service program aims to evaluate the effectiveness of the Introduction to Campus Life Program for New Students (PKKMB) at the Faculty of Social and Political Sciences, Mulawarman University, class of 2024. The implementation of this activity was attended by 696 students of the Faculty of Social and Political Sciences, Mulawarman University, class of 2024. The instrument used in this community service program was a questionnaire in the form of a Google form, which was distributed from August 12 to August 22, 2024. The results of this community service program showed that shouts and togetherness were the most memorable moments. The participants enjoyed interaction with new friends, creative performances, and collaboration between study programs. Although the PKKMB event was considered positive, several aspects needed improvement, including the comfort of the facilities, food quality, and time management. Recommendations include improving refrigeration facilities, consumption quality, and setting more efficient schedules. Overall, although there were several technical and operational suggestions for improvement, respondents showed a high level of satisfaction with this PKKMB event and praised the committee for their responsive and friendly performance.